PENERAPAN METODE EKSPERIMEN PERUBAHAN WUJUD UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Ismijati Ismijati (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
The purpose of this study was to improve student learning outcomes by using experimental methods on the material of changing the shape of objects in science learning. This research is a classroom action research (CAR) with a sample of fifth grade students at SDN Semolowaru I Surabaya. The instruments used include tests, observation sheets, and questionnaire sheets, where it is hoped that through this experimental method, students will learn and experience for themselves so that it can more easily improve students' understanding. The results of the application of this experimental method showed that in the first cycle student learning outcomes with a percentage of 76% and student activity by 72%. In Cycle II through the experimental method, there was an increase, namely student learning outcomes to 88% and student activity increasing to 90%. From the data analysis and research results, it can be concluded that the application of the experimental method can improve student learning outcomes for material change